2021
DOI: 10.1002/asi.24592
|View full text |Cite
|
Sign up to set email alerts
|

Fairness in digital sharing legal professional attitudes toward digital piracy and digital commons

Abstract: Contrary to a popular belief of lawyers having the most strict perception of law, law professionals actually strongly skew toward more favorable views of digital sharing. According to our qualitative study, relying on in‐depth interviews with 50 Harvard lawyers, digital piracy is quite acceptable. It is considered fair, especially among friends and for noncommercial purposes. We argue that this not only can indicate that the existing law is becoming outdated because of its inability to be enforced, but also th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 80 publications
1
1
0
Order By: Relevance
“…The study found that students were generally aware of the importance of respecting digital law and avoiding illegal activities such as hacking, piracy, and cyberbullying. This finding was also reported by Ciesielska and Jemielniak [47] who investigated college students' attitudes toward digital piracy. The study found that while students were generally aware that digital piracy is illegal, many of them were still engaged in piracy due to the convenience and affordability of pirated content.…”
Section: Digital Lawsupporting
confidence: 84%
“…The study found that students were generally aware of the importance of respecting digital law and avoiding illegal activities such as hacking, piracy, and cyberbullying. This finding was also reported by Ciesielska and Jemielniak [47] who investigated college students' attitudes toward digital piracy. The study found that while students were generally aware that digital piracy is illegal, many of them were still engaged in piracy due to the convenience and affordability of pirated content.…”
Section: Digital Lawsupporting
confidence: 84%
“…This is the result of research conducted worldwide by psychologists, sociologists, and media educators (Smahel et al, 2020;Pyżalski et al, 2019;. Emerging research findings reveal not only the scale of the phenomenon of selected risk behaviours, but also the mechanisms hidden behind typical e-risks, such as cyberbullying, cyberaggression (Del Rey et al, 2015;Dvoryanchikov et al, 2020), online image protection, digital piracy (Ciesielska & Jemielniak, 2021), and problematic use of smartphones (Kopecký et al, 2021). The analysis of individual phenomena usually takes place within the framework of diagnostic research assigned to the risk paradigm of media pedagogy, where individual e-risks constitute a separate pool of risk behaviours.…”
Section: Introductionmentioning
confidence: 99%